Method for determination of glufosinate ammonium residue in palm oil and water samples using high performance liquid chromatography with flourescence detector - Ahmad Faaudzi, Muhammad Danial (2016)
New method for determination for glufosinate ammonium residues in crude palm oil (CPO), crude palm kernel oil (CPKO) and water samples using high performance chromatography with fluorescence detector (HPLC-FLD) was investigated. The first part of the thesis studied the development of glufosinate ammonium extraction from water sample. In the preliminary study on the extraction technique, several types of SPE were evaluate for the suitability of the sorbent to retain the glufosinate ammonium compound. The SPE SAX/NH2 was the most suitable and stable to be used for the extraction. The extraction was done using SPE SAX/NH2 connected to the SPE vacuum manifold to assist the elution of the solvent through the cartridge. The cartridge was first precondition with 3ml of methanol and 5mL of water (pH 7). Then a known amount of standard glufosinate ammonium was injected and 100 mL of ultrapure water (pH 7) was allowed to flow through the SPE cartridge. The cartridge was then eluted with 5 mL of KH2PO4 solution (pH 6-7). The elution solution was collected in a vial and derivatized using 9-fluoronylmethylchloroformate (FMOC-Cl).The implement of solid phase extraction (SPE) SAX/NH2 was able to handle up to 1L volume of water sample in preconcentration process makes this method applicable to be used in real water sample. The percentage recovery for glufosinate ammonium in water sample were in the range 82 to 113% with RSD below 10.The limit of detection was 0.03 μg ml-1 and limit of quantification of this method was 0.1 μg ml-1. Glufosinate ammonium extraction from CPO and CPKO samples was conducted by liquid-liquid extraction (LLE). Preliminary study to determine the most suitable solvent for sample spiking was conducted. The mixture of acetone: water with ratio of 70:30 was the most suitable solvent mixture for the sample spiking solution. Comprehensive investigation in order to select the appropriate solvent extraction in LLE was done. The outcome from the test showed that water and dichloromethane was the best solvent to be used in LLE for the extraction of glufosinate ammonium compound from CPO and CPKO samples. This method gave a good extraction and high recovery ranging from 86-112% for CPO sample and 80-81% for CPKO sample. The RSD also showed good accuracy and repeatability with all the values obtained was below 10. The optimized method also went through the validation test. Both developed methods gave good linearity, accuracy, precision, LOD, LOQ and ruggedness. The method linearity correlation coefficient was 0.9994 and 0.9997 for oil and water sample respectively at concentrations ranging from 0.05 to 1.0 μg ml-1. The limit of detection and limit of quantification of this method were found to be 0.03 and 0.1 μg ml-1, respectively. The research findings suggest that this method could be considered as reliable for the determination of glufosinate ammonium in palm oil for food safety evaluation and water sample.